La crisis del sector eléctrico en california 2000–2001: reformas y desintegración vertical (2005)
This paper seeks to analyze what factors determine the capital structure of the banking firms in Colombia. With this purpose, the existing literatura about the subject is reviewed and, assuming that the hypothesis of the existence of an optimal capital structure holds, an optimization model of a representative banking firm is implemented to observe how these factors affect the optimal capital structure. Additionally, a panel data model is run to contrast the theoretical results with the empirical evidence for the Colombian banking firms. Finally, some conclusions about the found results are postulated.